Sauropod diversity (Dinosauria: Sauropoda) of Cerro Overo – La Invernada (Bajo de la Carpa Formation, Santonian), northeastern Neuquén Basin, and paleoecological implications for Upper Cretaceous sauropod faunas - Filippi, Leonardo Sebastián (2024)
The Upper Cretaceous fossil vertebrate fauna of the Bajo de la Carpa Formation (Santonian), derived from several different locations in the Neuquén Basin, is relatively abundant and diverse, comprising mainly small to medium-sized reptiles, birds and fishes. The Cerro Overo – La Invernada locality (CO – LI), in the north of the basin, records a similar faunal component for that age, but stands out for its relatively greater abundance and diversity of titanosaur sauropods. The study of the materials presented here allows us to establish the presence of specimens of sauropods other than Overosaurus, the only titanosaur recorded so far in the area, the coexistence of small–medium sized forms with larger forms, which in turn represent some forms with more basal characteristics and others with more derived features. The abundance of the record of sauropods in CO – LI shows both morphological and evolutionary variations, so the discovery of more complete specimens will allow paleofaunistic, paleobiological, and paleoecological studies to be carried out. This will provide a better understanding of the role of titanosaurian sauropods in Late Cretaceous ecosystems.